Assessment of the feed additive consisting of l‐valine produced by fermentation with Corynebacterium glutamicum KCCM 80058 for all animal species for the renewal of its authorisation (CJ Europe GmbH) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Roberto Edoardo Villa; Giovanna Azimonti; Eleftherios Bonos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Ronette Gehring; Boet Glandorf; Maryline Kouba; Marta López‐Alonso; Francesca Marcon; et al. (EFSA Journal, 2025)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the assessment of the application for the renewal of the authorisation of l‐valine produced by fermentation with a genetically modified strain of Corynebacterium glutamicum KCCM 80058 as a nutritional feed additive for all animal species. The additive is authorised for use in all animal species (3c370). The applicant has provided evidence that the additive currently in the market complies with the existing conditions of authorisation. The EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) concluded that the use of the feed additive in animal nutrition remains safe for the target species, consumers and the environment. As regards the safety for the user, l‐valine produced by C. glutamicum KCCM 80058 is not an irritant to skin or eyes nor a skin sensitiser. The present application for renewal of the authorisation does not include any modification proposal that would have an impact on the efficacy of the additive and therefore there is no need for re‐assessing the efficacy.